Enzymatic activity of Cyathus olla during solid state fermentation of canola roots - Shinners-Carnelley, T.C.; Szpacenko, A.; Tewari, J.P.; Palcic, M.M. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 2002)
Cyathus olla, a bird's nest fungus, is being studied as a biological control agent of stubble-borne diseases of canola. Our objectives in this study were to detect and identify plant cell wall degrading enzymes produced by C. olla during solid state fermentation of canola roots. We identified laccase and manganese peroxidase in both 1- and 4-week incubations, and aryl-alcohol oxidase was detected following 4 weeks of incubation. Crude buffer extracts were assayed for cellulases and polygalacturonase, but only the latter was detected. We conclude that C. olla has enzymes to degrade lignin and that it may have use as an inoculant to accelerate stubble decomposition.